Advanced uterine papillary serous cancer: Could there be a role for newer targeted therapeutic approaches or immune checkpoint inhibitors?. (July 2021) - Dasanu, Constantin A; Lerner, Jaren; Ocampo, Miguel Michel; Iskandar, Andrew S; Kaur, Jaspreet; Tuler, Shahat; Codreanu, Ion; Farrell, Stephanie; Plaxe, Steven C
Background: Although now available in oncology clinics, comprehensive germline mutation testing is being performed only in a minority of patients with advanced uterine papillary serous cancer (UPSC). Some of these patients might harbor various targetable mutations, either heritable or acquired. Data sources: We conducted a retrospective cohort study involving all consecutive patients with UPSC treated at our institution from 2009-2019. Data on epidemiology, with an accent on personal and family history of cancer, clinical presentation, disease stage, employed treatment modalities and cancer-specific survival (CSS) was sought. Findings: Thirteen patients were seventy years of age or younger (≤70) while 15 were older than seventy (>70), and the two arbitrary patient cohorts were well-balanced for the TNM stage. Four UPSC patients >70 had a personal history of metachronous breast cancer. We also identified five cases of breast cancer, two cases of colon cancer, and one of each ovarian and uterine cancer in the first-degree relatives of UPSC patients >70. More than 90% of patients had surgical excision/debulking, and nearly half of the patients in each group received systemic chemotherapy. The most common chemotherapy regimen was carboplatin-paclitaxel every three weeks. Compared to patients ≤70, the UPSC patients >70 were less likely to undergo postoperative radiation therapy (6% vs 61.5%; p = 0.001) and had a worse CSS (21.8 vs. 27.4 months; HR 0.61, p = 0.03). Conclusions: Personal and family history in a cohort of older UPSC patients identified an excess of second primary cancers, and these patients displayed a shorter CSS. Comprehensive germline and tumor mutation analysis might identify optimal candidates for various targeted agents and immune checkpoint inhibitors, and ultimately improve survival. This may represent an unmet need in the UPSC patients, and further studies are needed to confirm the significance of our findings.